2011
DOI: 10.1021/jp111552f
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Sensitive Sum Frequency Revealing Accommodation of Bicarbonate Ions, and Charge Separation of Sodium and Carbonate Ions within the Air/Water Interface

Abstract: Interfacial water structure plays a key role in many chemical, biological, and environmental processes. Here, in addition to conventional VSFG, we employ phase-sensitive sum frequency generation (PS-SFG) to investigate the average direction of the transition dipole of interfacial water molecules that is intrinsically contained in the sign of the second-order nonlinear susceptibility, χ((2)). The orientation of water at air/aqueous inorganic salt interfaces of Na(2)CO(3) and NaHCO(3) was inferred from the direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
76
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(87 citation statements)
references
References 50 publications
11
76
0
Order By: Relevance
“…Recent tomographic work has demonstrated that interferometric detection of SHG signals gives access to phase information that cannot be probed with conventional SHG imaging. 27,29,43 Indeed, our observation is in concert with recent phase sensitive SHG measurements on collagen (through private communication with François Légaré, Institut National de la Recherche Scientifique, Centre Énergie Matériaux et Télécommunications, Canada). Nonetheless, phase-sensitive SFG enables a direct identification of the molecular modes whose differences in orientation are responsible for the sign reversal, providing a more complete molecular picture than what can be obtained with SHG.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Recent tomographic work has demonstrated that interferometric detection of SHG signals gives access to phase information that cannot be probed with conventional SHG imaging. 27,29,43 Indeed, our observation is in concert with recent phase sensitive SHG measurements on collagen (through private communication with François Légaré, Institut National de la Recherche Scientifique, Centre Énergie Matériaux et Télécommunications, Canada). Nonetheless, phase-sensitive SFG enables a direct identification of the molecular modes whose differences in orientation are responsible for the sign reversal, providing a more complete molecular picture than what can be obtained with SHG.…”
Section: Discussionsupporting
confidence: 84%
“…It was previously shown in macroscopic SFG spectroscopic experiments that phase sensitive (PS) detection allows a direct measurement of the amplitude and phase of vibrationally resonant χ (2) components. 2427 Here, we extend this principle to microscopic examination of collagen tissue, providing information on the effective polarity of the collagen fibrils within the probing volume. Using PSVR-SFG, we show that the methylene mode exhibits a highly conserved orientation within individual bundles of fibrils.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, this has been overcome by the use of broadband lasers and the collection of the entire spectrum using heterodyne-detected (HD) SHG 19,20 and SFG spectroscopy. [21][22][23][24][25][26][27][28][29][30] In this, the signal and local oscillator are separated in time at a fixed delay and the interference is essentially measured in the frequency domain. By back-Fourier transformation, filtering and forward-Fourier transformation, the real and imaginary parts of the non-linear susceptibility can be measured across a spectral range.…”
Section: Introductionmentioning
confidence: 99%
“…[83][84][85][86] The differential Imχ (2) S spectra for different salts with respect to that of neat water are presented in Fig. 12.…”
Section: Studies Of Ion Adsorption At Water/air Interfacesmentioning
confidence: 99%